Effects of ketoconazole and valproic acid on the pharmacokinetics of the next generation NNRTI, lersivirine (UK‐453,061), in healthy adult subjects - Langdon, Grant; Davis, John; Layton, Gary; Chong, Chew‐Lan; Weissgerber, Georges; Vourvahis, Manoli (British journal of clinical pharmacology, 2012)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Lersivirine (UK‐453,061) is predominantly cleared by glucuronidation (UGT2B7) and oxidation via cytochrome P450 (CYP) 3A4. • Lersivirine metabolism, and thus pharmacokinetics, may be affected by concomitant administration of drugs affecting CYP3A4 and UGT2B7. • Ketoconazole is a potent inhibitor of CYP3A4 and an inhibitor of UGT2B7. Valproic acid is a potent inhibitor of UGT2B7. WHAT THIS STUDY ADDS • Combined inhibition of CYP3A4 and UGT2B7 with ketoconazole increases the exposure of lersivirine, and may warrant lersivirine dose adjustment to compensate for this interaction. • Inhibition of UGT2B7 with valproic acid does not have a substantial effect on lersivirine pharmacokinetics. AIMS To investigate the effect of inhibitors of cytochrome P450 (CYP) 3A4 and glucuronidation (UGT2B7) on the pharmacokinetics of lersivirine (UK‐453,061), a next generation non‐nucleoside reverse transcriptase inhibitor with a unique resistance profile, and to investigate the safety and tolerability of co‐administration of lersivirine with these inhibitors. METHODS Two open‐label, randomized, placebo‐controlled, crossover studies were conducted in healthy subjects. Study 1 investigated the effect of ketoconazole (400 mg once daily) on the pharmacokinetics of lersivirine (250 mg once daily). Subjects received ketoconazole 400 mg once daily or placebo on days 1–2 and received lersivirine 250 mg once daily and ketoconazole 400 mg once daily or placebo on days 3–9. Study 2 investigated the effect of valproic acid (VPA, sodium valproate, 1000 mg once daily) on the PK of lersivirine (500 mg once daily). On days 1–7, subjects received lersivirine 500 mg once daily plus either VPA 1000 mg or placebo. RESULTS Compared with lersivirine alone, co‐administration with ketoconazole increased the lersivirine mean area under the curve (AUC(0,24 h)) and maximum plasma concentration (Cmax) by 82% (90% CI 74%, 91%) and 61% (90% CI 41%, 83%), respectively. VPA increased the mean lersivirine AUC(0,24 h) by 25% (90% CI 16%, 35%), with little effect on Cmax (2.5%, 90% CI −9%, 16%). There were no serious adverse events and no treatment‐related discontinuations from either study. CONCLUSIONS Inhibition of CYP3A4 and UGT2B7 by ketoconazole increased lersivirine exposure. Inhibition of UGT2B7‐mediated glucuronidation by VPA had a modest effect on lersivirine exposure. Co‐administration of lersivirine with either ketoconazole or VPA appeared to be well tolerated.